Analysis Of Effect Of Social And Economic Infrastructure Development To The Economy Of Coastal Areas In East Java Province - Gigih Pratomo (LPPM of NAROTAMA UNIVERSITY, 2017)
Developing countries are always faced with various economic development challenges (Todaro, 2000). Development of social economic Infrastructures has an important factor to influence the level of Gross Domestic Product. In coastal areas, infrastructure development is low and not optimal utilization. This study aims to determine the effects of development of social economic Infrastructures to the economy of coastal area in East Java Province during the perion 2008-2015. This study uses secondary data and samples taken by purposive random sampling technique that is the district/city of Banyuwangi, Jember, Probolinggo, Trenggalek, Sumenep, Sampang, Bangkalan, Lamongan, Gresik, Malang, dan kota Surabaya. This study uses panel data Fixed Effects Model (FEM) method with Generalized Least Square (GLS) cross section weight.The results of this study indicate that the variable of number school building, roads, and electricities significantly and positively effect to the economy of coastal area in East Java Province.